Behaviour of RC Columns Retrofitted Using Geopolymer Concrete - Pandey, Himanshu (My University, 2017)
The corrosion of concrete is most significant durability problem in the world of civil engineering. Concrete structures in coastal areas and aggressive environments are constantly exposed to various corrosive substances. Out of these various substances, sulphates are most deteriorating ones. These can cause reduction in strength, spalling, expansion or mass loss in concrete. Hence, post damage retrofitting of these structures has become a necessity for concrete to serve up to its service life. The present work aims to study the behaviour of RCC columns of different slenderness ratios which are exposed to sulphate attack and then retrofitted using geopolymer concrete. Geopolymer Concrete represents a class of alkali activated system in which activation of aluminosilicate source like fly ash is done by alkaline activators like sodium silicate and sodium hydroxide. The final end product of this reaction is a 3-D polymer chain and ring structure containing Si-O-Al-O bonds. To carry out the dissertation work, 21 specimens of each slenderness ratio i.e. 3 (100mm dia. x 300 mm ht.), 6 (100 mm dia. x 600 mm ht.) and 12.5 ( 100 mm dia. x 1250 mm ht.) were casted. Out of these 21 specimens of each slenderness ratio, 3 numbers of specimens were control specimens to study the behaviour of RCC columns having different slenderness ratio. To study the effect of sulphate attack on RCC columns, 3 number of samples of each slenderness ratio were kept immersed in 2%, 5% and 7% (by weight of water) sodium sulphate solution. Chemical analysis was also performed on these damaged specimens to study the depth of sulphate intrusion in concrete. To study the effect of retrofitting, 3 specimens of each slenderness ratio damaged by different sulphate solutions were retrofitted using Geopolymer concrete. The geopolymer concrete used in for retrofitting was developed after reviewing past literature to understand its reaction mechanism and suitably selecting the proportions for experimental work. The Geopolymer concrete used for retrofitting purpose is a calcium-alumino-silicate system comprising of Flyash, GGBS and Glass Powder. The alkali used for activation is sodium hydroxide. Testing of these specimens was done according to standard procedures defined by IS codes. From the results obtained for control columns, it was found that as the slenderness ratio increases, the load carrying capacity of RCC columns decreases. From the results obtained for RCC columns exposed to sulphate attack, it was found that exposure to sulphate solution has a great influence on the load carrying capacity of columns. It was observed that as the sulphate ion concentration increases, the load carrying capacity of RCC columns decreases. This was further confirmed from the results of chemical analysis. On testing specimens after retrofitting, it was found that the strength of columns was restored up to a certain extent. The load deflection behaviour of retrofitted specimens was found similar to the control specimens. However, for retrofitted samples the load carrying capacity was found to be slightly lower than that of control specimens.
Keywords: Retrofitting, Sulphate attack, Geopolymer concrete, columns